2021
DOI: 10.1097/sla.0000000000004371
|View full text |Cite
|
Sign up to set email alerts
|

End Colostomy With or Without Mesh to Prevent a Parastomal Hernia (GRECCAR 7)

Abstract: Objective: To evaluate whether systematic mesh implantation upon primary colostomy creation was effective to prevent PSH. Summary of Background Data: Previous randomized trials on prevention of PSH by mesh placement have shown contradictory results. Methods: This was a prospective, randomized controlled trial in 18 hospitals in France on patients aged !18 receiving a first colostomy for an indication other than infection. Participants were randomized by blocks of random size, stratified by center in a 1:1 rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 27 publications
5
55
0
Order By: Relevance
“…[Correction added on 05 October 2021 after first online publication: In the preceding line, >-0.97 and >-0.94 hve been corrected to >-0.95 and >-0.93 respectively in this version.] We note that three [5,34,44] of the four largest multicentre RCTs did not provide strong evidence to exclude the possibility that synthetic mesh has no effect in reducing the incidence of PSH. In contrast, the fourth RCT [2] reported a much lower rate of PSH incidence in the group who received prophylactic mesh.…”
Section: Discussionmentioning
confidence: 83%
“…[Correction added on 05 October 2021 after first online publication: In the preceding line, >-0.97 and >-0.94 hve been corrected to >-0.95 and >-0.93 respectively in this version.] We note that three [5,34,44] of the four largest multicentre RCTs did not provide strong evidence to exclude the possibility that synthetic mesh has no effect in reducing the incidence of PSH. In contrast, the fourth RCT [2] reported a much lower rate of PSH incidence in the group who received prophylactic mesh.…”
Section: Discussionmentioning
confidence: 83%
“…Excluding the RCT by Jänes et al [43] from the primary meta-analysis yielded a slightly higher RR of 0.62 (0.45-0.83) (I 2 = 58%; P < 0.01; Figure S15 in Appendix S1). Combining the two largest multicentre RCTs [5,36] with blinded outcome assessment produced an RR of 0.95 (0.73-1.25) (I 2 = 0%; P < 0.77; Figure S16 in Appendix S1), which indicates no significant difference in treatment effect between the mesh and no mesh groups.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…In another sensitivity analysis, the RCT by Jänes et al [43] was excluded from the primary meta-analysis since it was the only RCT with a follow-up period of 60 months. In the final sensitivity analysis, the two largest RCTs [5,36] with low risk of detection bias (blinding of outcome assessment) were pooled together.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…One‐year follow‐up data on 201 Scandinavian patients showed no difference in parastomal hernia rates using either a cruciate fascial incision, circular incision or prophylactic mesh [1]. A well‐performed French multicentre trial has recently shown mesh to be of little value in preventing parastomal herniation (PSH) in the first 2 years [2].…”
mentioning
confidence: 99%